2016
DOI: 10.1039/c5fd00148j
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic response to cisplatin-like drugs in human breast cancer cells probed by vibrational microspectroscopy

Abstract: Studies of drug-cell interactions in cancer model systems are essential in the preclinical stage of rational drug design, which relies on a thorough understanding of the mechanisms underlying cytotoxic activity and biological effects, at a molecular level.This study aimed at applying complementary vibrational spectroscopy methods to evaluate the cellular impact of two Pt(II) and Pd(II) dinuclear chelates with spermine (Pt 2 Spm and Pd 2 Spm), using cisplatin (cis-Pt(NH 3 ) 2 Cl 2 ) as a reference compound. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 62 publications
10
87
0
Order By: Relevance
“…Indeed, this polynuclear Pd(II) complex is therefore shown to be a very promising antitumour agent, corroborating previous studies by the authors published by our group in other cells lines such as MCF-7 [12] reporting a high impact on proteins and DNA backbone [41] as compared to its Pt(II) homologue and cisplatin, as well as a significant effect on cell morphology particularly targetting the cytoskeleton (mostly the microtubules, [12]), that may explain, at least in part, the anti-angiogenic effect presently observed associated to the inhibition of tubular-like structure formation [37]: these compounds have been shown to display a higher cytotoxicity towards breast cancer (namely TNBC [12]), due to a more severe DNA damage via long-range interstrand drug–DNA adducts not available to conventional drugs [42]. …”
Section: Discussionsupporting
confidence: 87%
“…Indeed, this polynuclear Pd(II) complex is therefore shown to be a very promising antitumour agent, corroborating previous studies by the authors published by our group in other cells lines such as MCF-7 [12] reporting a high impact on proteins and DNA backbone [41] as compared to its Pt(II) homologue and cisplatin, as well as a significant effect on cell morphology particularly targetting the cytoskeleton (mostly the microtubules, [12]), that may explain, at least in part, the anti-angiogenic effect presently observed associated to the inhibition of tubular-like structure formation [37]: these compounds have been shown to display a higher cytotoxicity towards breast cancer (namely TNBC [12]), due to a more severe DNA damage via long-range interstrand drug–DNA adducts not available to conventional drugs [42]. …”
Section: Discussionsupporting
confidence: 87%
“…[16,17] Raman microspectroscopy, in particular, is a cutting-edge technique that enables an accurate and non-invasive profiling of biological samples of several types (e.g., plants, human cells, or tissues), virtually without interference from water, yielding unique chemical fingerprints. [18][19][20][21] Actually, the high sensitivity and subcellular spatial resolution of microRaman allows us to detect the smallest chemical variations and conformational rearrangements even in heterogeneous biological models such as leaves, fruits, or seeds. In turn, FTIR in attenuated total reflectance mode (FTIR-ATR) is particularly suitable for routine analysis because it is easily accessible, inexpensive, fast, and requires no sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…The dinuclear complexes Pt 2 Spm and Pd 2 Spm have been studied by the authors in the last few years and have been shown to act as promising anticancer agents towards human metastatic breast cancer (Batista de Carvalho et al, 2016a, Batista de Carvalho et al, 2016b, Fiuza et al, 2011, Marques et al, 2002, Silva et al, 2013 and osteosarcoma (Lamego et al, 2017). A multidisciplinary study was presently carried out to attain complementary structural and dynamical information on their interplay with DNA (their main pharmacological target), using QENS measurements, SR-FTIR and SR-EXAFS/XANES.…”
Section: Discussionmentioning
confidence: 99%
“…These results, including complementary data regarding the lower frequency spectral range not previously probed, are in good accordance with the information formerly obtained (by EXAFS, FTIR, Raman and INS) for DNA´s purine bases upon cisplatin binding. (Batista de Carvalho et al, 2016b In addition, valuable information was gathered on a different interplay with the nucleic acid regarding the dinuclear agents Pt 2 Spm and Pd 2 Spm as compared to the mononuclear (clinically used) drug cisplatin.…”
Section: Qensmentioning
confidence: 99%
See 1 more Smart Citation